1991
DOI: 10.1007/bf00011883
|View full text |Cite
|
Sign up to set email alerts
|

Correcting iron deficiencies in annual and perennial plants: Present technologies and future prospects

Abstract: Correction of Fe chlorosis is done mainly by foliar sprays because soil applications generally are ineffective, especially for annual crops. Inorganic Fe sources applied to soils react rapidly to forms which are not as available to plants; ferrous Fe is oxidized to the ferric form in well-aerated soils, especially as soil pH increases. Several synthetic chelates and organic complexes have been used with varying success, depending upon Fe source and rate, application method, plant species, and weather and soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…It reduces crop quality and depresses crop yields and hence causes economic losses. In particular in alkaline and calcareous soils, the bioavailability of iron can be severely limited (Chaney 1984;Mortvedt 1991). This mainly results from the low solubility of iron (hydr)oxides at high pH (Lindsay 1979), and from the elevated bicarbonate concentration in the soil solution (Boxma 1972;Mengel et al 1984;Shi et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It reduces crop quality and depresses crop yields and hence causes economic losses. In particular in alkaline and calcareous soils, the bioavailability of iron can be severely limited (Chaney 1984;Mortvedt 1991). This mainly results from the low solubility of iron (hydr)oxides at high pH (Lindsay 1979), and from the elevated bicarbonate concentration in the soil solution (Boxma 1972;Mengel et al 1984;Shi et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In calcareous soils, which constitute the major part of cultivated land, the soil solution does not provide more than 10% of the plant requirements for Fe (MORTVEDT, 1991). The total Fe content in these soils is high but the available fraction for the plant is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…However, Helms et al (2010) suggested that the tolerant variety is not necessarily the best selection, and is oft en better to plant a variety with high yield potential outside of zones with severe Fe defi ciency. Mortvedt (1991) found that adding FeSO 4 to the furrow increased yields and reduced chlorosis, however inorganic Fe sources quickly become unavailable, and may not be economical. Foliar Fe application, especially of chelated forms, has been inconsistent, being successful at some locations in reducing signs of chlorosis (Goos and Johnson, 2000) and increasing yield in some cases (Penas et al, 1990).…”
mentioning
confidence: 99%